Diagnosis dan Tata Laksana Kardiomiopati Peripartum: Tinjauan Pustaka - Veronica Winda Soesanto; Billy Jonathan (Cermin Dunia Kedokteran, 2025)
Peripartum cardiomyopathy is a cardiac disorder with shortness of breath as the main symptom but often late diagnosed due to resemblance to normal condition of late gestation. The causes of peripartum cardiomyopathy are multifactorial including ages, races, genetics, and preeclampsia. Peripartum cardiomyopathy needs early diagnosis and appropriate management to reduce the risk of cardiac complications and to improve the quality of life for both mother and child.